Resolução de problemas nos processos de ensino de Matemática na Educação Básica: uma proposta com alunos do 6º ano do ensino fundamental - Amaral, Andre Silveira do (2023)
Mathematical problem-solving is a teaching and learning methodology that enables students to construct their mathematical thinking. In this process, the teacher serves as a learning mediator and actively cooperates to provide learners with the opportunity to mobilize knowledge of mathematical concepts and procedures. The present study aimed to investigate how the teaching and learning methodology of problem-solving, proposed by George Polya, assists 6th-grade elementary school students in mobilizing mathematical knowledge to solve various types of mathematical problems. The research was qualitative, naturalistic, or field-based, involving students from Muqui municipal school, in the southern region of Espírito Santo. Data collection occurred through three stages: the application of the first set of problem situations; socialization; and the application of the second set of problem situations. The data obtained were analyzed using the four phases of the problem-solving process theory defined by Polya (2006). The studies demonstrate that problem-solving in the teaching of Mathematics is most effective when it is primarily based on the understanding of concepts and the existence of the phases leading to solution, including understanding, planning, plan execution, and, finally, reflection. Therefore, teaching Mathematics through contextualized problem-solving should be seen as an opportunity to educate, and formal content should be addressed through context-based themes from the students’ environment, constantly stimulating their imagination and encouraging them to create their own problem-solving strategies.